COMPARATIVE CHARACTERISTICS OF MAIKOP SERIES OF CASPIAN-BLACK SEA REGION - Mykhailov, V. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The features of the geological structure and composition of the Maikop series of the southern margin of the East European platform are considered in the paper. The sections of the Maikop series of Black Sea and the Crimean region, including the north-western shelf of the Black Sea (wells Arkhangelsk-21, Golitsyn-1, 6, 7, 9, 12, 28); the central part of the Crimean peninsula (Dzhankojsky-1.); the Kerch Peninsula (Fontanovskaya-6, 12.); the shelf of Azov Sea (Yuzhnokazantipskaya-3.); Prykerchenska part of Black Sea shelf (Subbotina-1) are described. Comparative characteristic of the Maikop series in such regions: the Kerch-Taman trough, the eastern part of the Black Sea, the Indol-Kuban Trough, West, Central and East Caucasus, the Middle Caspian, West Azerbaijan, South-Caspian depression are given. Oligocene-Miocene Maikop series is widely distributed in the south of East European platform. It is represented by series of gray and dark gray mudstone weakly calcareous argillites, sometimes interbedded with siltstone, sandstone, fine-grained sands, rich in organic matter (from 0,69 to 10,23 %), Corg (2,20–16,70 %), the porosity of which varies widely – from 0,3 to 31,7 %. They are associated with numerous deposits of hydrocarbons, as well as phosphorus, rare earth-uranium deposits. The section of the series is dominated by argillites, where the amount of sand and silt material does not exceed 20 %, but sandstone, siltstone and sand layers that are from 10 to 100 m in width, are treated as reservoir rocks for traditional hydrocarbon deposits. Patch of clays that is 15–100 meters thick and separate them, serve as caprock. As a whole, Maikop sandy clay series is the regional screen for collectors confined to the formations occurred below. Distribution Corg enriched lithotypes in the Maikop section is of uneven nature and is primarily influenced by paleooceanographic sedimentation factors. It is possible to predict the formation of several age levels of sedimentations with enrichment in Corg. They form rock series ranging from 20 to 100 m in thickness and, occurrence depths from 300 to 1,500 m. However, the degree of thermal transformation of rocks is extremely low. Organic matter of Maikop series is typically immature and, shows relatively high temperatures of pyrolysis (418–423 oC) that indicates, on low depth, subsidence of host rocks (up to 1,5–2,0 km), while the main zone of oil formation is located at depths of 3–6 km.
Keywords: Oligocene; Miocene; Maikop series; hydrocarbons